ANALYSIS OF THE CONCEPT OF SOCIAL ORPHANHOOD AND THEORIES AIMED AT ITS STUDY - Ziyaeva X. O.; Mingbayeva Bashorat Jalgashboevna (Journals Park Publishing, 2023)
In this article, the concept of social orphanhood, the causes of the origin of social orphanhood and measures aimed at preventing it, scientific theories that have been studied for centuries, comprehensive support for socially orphaned children, specific features of social assistance are classified in detail.
Keywords: Orphan children, social orphanhood, social assistance, Social Psychology, kemticity, socialization, upbringing.